Sustainable business solutions for traditional handicraft product in the Northwestern provinces of Vietnam - Hai Nguyen Thuy; Duong Nguyen Thuy; Huy Dinh Tran Ngoc; Hien Dinh Thi (Zielona Góra: Faculty of Economics and Management Press)
Local tourism development requires us to consider many solutions, among them is sustainable solutions for business development of traditional handicraft products. This study is done based on surveys of northwestern provinces of Vietnam, in which authors use statistics, questionnaires and charts. Research findings show us that despite of potential chances, tourism activities still mainly exploit the value of available natural resources, are heavily spontaneous, lack of planning, small-scale tourism business, lack of creativity and diversity in tourism activities. services, infrastructure and quality of tourism service are limited. Our study also indicated that macro factors affect tourism activities.
Keywords: traditional handicraft products; business development; tourism; sustainable development; Vietnam; North-Western Provinces; tradycyjne wyroby rękodzielnicze; rozwój biznesu; turystyka; rozwój zrównoważony; Wietnam; prowincje północno-zachodnie